KAJIAN SISTEM AGRIBISNIS HULU DAN PEMASARAN SAYURAN DI KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Harianti Harianti; Sitti Rosmalah; Nurmaya (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
This research was conducted in Konda District, South Konawe Regency with the aim of: to describe the implementation of the upstream agribusiness system and marketing of vegetables. The research method used is descriptive and qualitative data analysis using a Likert scale. The population in this study were all vegetable farmers in Konda District, namely in Lawoila Village with a total of 231 people and a sample of 58 people who could represent the actual state of the population with the Slovin formula. The results showed that the implementation of the upstream agribusiness system and marketing of vegetable agribusiness was already running, with several indicators in the upstream agribusiness subsystem such as the use of superior seeds with an index value of 88.10, on land 95.40 for the use of organic fertilizers 67.24 and inorganic 67. 82 and workforce 86.55 with an overall index score of 81.47%. Furthermore, in the marketing subsystem there are still several indicators that have not been maximized. As for the indicators, the index value at harvest was 82.18, transportation was 98.16, the use of tools was 96.03, the market was 45.17, and pricing was 50.43 with the overall index value reaching an index value of 69.72%. This shows that the implementation of the vegetable agribusiness system in the upstream agribusiness subsystem and marketing subsystem has been running, but there are still some indicators that the value is not maximized.